Workplace learning of new engineers in an automotive industry - Chan, Yuen Fook; Balaraman, Selvam (2017)
Purpose - According to Smith (1996), research has proven that skills which are directly connected to the work and are obtained in the workplace are learned quicker, kept longer, and result in higher productivity than those acquired in the classroom. Hence, the study aimed to identify the key issues of workplace learning of new engineers in automotive industry.This paper explores to what extent the knowledge and skills acquired by the new engineers at the job have equipped them with job competency in the automotive industry.This study adopted a qualitative case study method to compare data from a private engineering college, a public university and an automotive manufacturing industry.The identified target groups include one human resource manager, six new engineering graduates, and 4 university lecturers.The finding shows that the training programs is essential to enhance specific knowledge and skills required by new engineers to perform a task at industry.The training programs are divided into two categories—formal and informal training—and each category consists of technical and non-technical training programs. Most of the training programs for the new engineers are technical and job related trainings conducted inhouse by internal trainers which seldom focus on personal development of soft skills.Overall, the orientation program served to introduce them to the organization’s culture, values and systems.Undeniably, new engineers’ training is essential to improve job performance in current job and to train new skills to improve productivity and to achieve the organization’s current and future goals.All the new engineers involved in this study have pointed out that the amount of new knowledge to be learnt in the industry at the beginning of their employment was overwhelming.Most of the new engineers complained that not all the trainings took place as briefed during the orientation program. There were excellent career development plans shown during orientation program, but the plans have not been not executed as desired.For the OJT to be effective, it should be organized with well-trained and dedicated coach at the workplace. Qualified coach can ensure the new recruits are trained well, and improve job performance in current job and acquire new skills to achieve the organization’s current and future goals. Methodology - Based on the nature of this study, the researcher has used a qualitative case study method to discover, understand, and explain in an in-depth manner the issues of workplace training of new engineers in automotive industry. The interview questions were adapted from Laulata (2007)’s study to suit the purpose of this study. One of the major automotive manufacturing industries located in the state of Selangor has been selected for the study.This Malaysian and Japanese joint venture company which was established in 1970 has been producing non-national cars for the local and foreign market. In order to gauge the information for this study, a total of six new engineers (coded as NE1 to 6), one human resource manager (coded as HRm) and two supervisors (coded as SV1 to 2) were selected for the interviews. Besides that, two lecturers were selected from a private college in Cyberjaya (coded as LEC1 to 2) and the other two were selected from public universities located in Klang Valley (coded as LEC3 to 4).Overall, there were six engineers, one human resource manager and two supervisors involved in this study.Findings - Most of the new engineers appreciate the knowledge and experience gained during the induction program. The induction program served to introduce them to the organization’s culture, values and systems. It was confirmed by Informant HRm that they conduct an induction program for all new recruits to introduce them to the new working environment. During the familiarization stage, they are exposed to the nature of their new work and taught how to execute identified tasks. The new recruits are also briefed about the existing organizational culture, values, vision, working conditions, safe working rules, processes and procedures and the organizations expectations from new engineers. Besides that, organizations also provide On-Job-Training (OJT) to new engineers for a period of 6 months and other formal training programs for self-development. New engineers’ training is essential to improve job performance in current job or to train new skills for a new job to improve productivity and to achieve the organization’s current and future goals.Almost all of the new engineers said that Toyota Business Practice (TBP) was one of the most important training programs that they had attended. “The most appropriate way to develop new engineers is through on-job training, whereby they are attached to their immediate superiors who are generally more experienced at a particular job. Immediate superior will act as a coach or mentor to build relationship, guide in daily task and personal development to enhance job performance and productivity.The mentors’ function is to eventually motivate them to acquire the right knowledge and skills and perform job as per required standard” (SV1, 1.2).